Poly(urethane) synthesized from 9-ethoxy-1,10-octadecanediol obtained by modification of palm oil oleic acid - Bunbun Bundjali; Muhammad Masykuri; Fitri Widya Hartanti; I Made Arcana (Journal of Mathematical and Fundamental Sciences, 2018)
Poly(urethane) (PU) as a prepolymer was prepared by polymerization of the diol compound (9-ethoxy-1,10-octadecanediol) and 4,4-methylen-bis phenyl isocyanate (MDI) under nitrogen atmosphere at 85 °C. The 9-ethoxy-1,10-octadecanediol was obtained by several reaction steps, i.e. epoxydation of oleic acid obtained from palm oil, ring-opening of oleic acid epoxide, and reduction of oleic acid ester. All compounds obtained in this work were characterized by chemical structure analysis (FTIR and 1H NMR), supported by analysis of iodine value, acid value, and hydroxyl value determined by titration methods and thermal analysis, especially for poly(urethane). The 9-ethoxy-1,10-octadecanediol as the diol compound for preparation of poly(urethane) was analyzed by FTIR, supported by hydroxyl numbers determined by titration. Poly(urethane-urea) (PUU) was obtained by addition of ethylene diamine as chain extender to poly(urethane). The thermal stability of poly(urethane-urea) is higher than that of poly(urethane). The addition of ethylene diamine as chain extender in poly(urethane) can improve the intrinsic viscosity of polymer to form poly(urethane-urea). These results are supported by chemical structure analysis.